EFL Students’ Perceptions in Using Instagram in English Language Learning - Aqira, Heyma (RETAIN, 2022)
In teaching-learning, teachers can use many instructional media, especially Instagram. Instagram as social media has influenced society, especially for high school students. This research investigates high school students' perceptions of using Instagram in English language learning. This research used a mixed-method sequential explanatory design with a close-ended web survey questionnaire given to 77 students from the 10th grade until 12th grade in two senior high schools in Gresik, East Java which implement social media in their teaching and learning activities. An interview is also needed to know the students' perception concerning the impact of using Instagram in language learning. The results showed that the students perceive Instagram as a tool for senior high school students to learn English and impact the learners to utilize the features in Instagram for a better cause in learning English. Instagram offers many opportunities for teachers and students since it has plenty of features to use, especially during online learning, making it easier and helpful to connect. In addition, Instagram can motivate the students to learn English from their peers and develop their English skills. By seeing the students' perspectives through the data results, Instagram is a good tool for learning English and connecting teachers and students during a pandemic.